Impact of the temperature process on the morphology of 3D temporary bonded wafers: Quantification and reducing of the effect. (December 2021) - Montméat, P.; Le Cocq, M.; Enot, T.; Zussy, M.; Fournel, F.
Abstract: 300 mm diameter thinned-down wafers are manufactured using temporary adhesive bonding. A thermoplastic adhesive and a silicon carrier are used to fabricate 100 μm thick silicon wafers. The impact of temperature on the thickness homogeneity of temporary bonded stacks is studied. From 150 °C up to 300 °C, the total thickness of the structure increases with the temperature. Moreover, its amplitude strongly increases with the thinned wafer stress and the adhesive thickness. On the contrary, it does not depend on the different interface adherence. The thinned wafer stress results in a significant peeling force which drives the deformation of the structure. This deformation is possible because of the high elasticity of the polymer at high temperature. To reduce this deformation, an alternative carrier is proposed yielding reduction of the adhesive thickness at the bonded edge only. Graphical abstract: Image 1 Highlights: We study the impact of the temperature on 3D temporary bonded stacks made of a thermoplastic adhesive. From 150 °C up to 300 °C, the total thickness of the structure increases with the temperature. The deformation amplitude of the structure strongly increases with the wafer stress and the adhesive thickness. When the temperature is high, the thermoplastic is elastic enough to allow the relaxation and deformation of the structure. An innovative carrier wafer is proposed to limit the bonded stack deformation at high temperatures.